Pengaruh Penggunaan Smartphone terhadap Perkembangan Personal Sosial Anak Usia Pra-Sekolah - Heni Heni; Ahmad Jalaludin Mujahid (Jurnal Keperawatan Silampari, 2018)
The purpose of this study was to determine the effect of the use of smartphones on the personal social development of pre-school age children in Al-Marhamah Kindergarten. This research uses quantitative research methods with cross sectional design. The results showed more than half of pre-school age children are smartphone users with frequent frequency with 24 children (72.7%). Less than half of pre-school-aged children experience doubtful development with a total of 15 children (45.5%). Statistical test results obtained p value of 0.017. Conclusion, there is a significant relationship between smartphone usage and the personal social development of preschool children in Al-Marhamah, Majaelngka Regency, 2017. Keywords: Pre-School Age Children, Personal Development, Smartphones